"Complete collection of laws of Russian empire" as a source of the history of the Crimean campaigns 1687–1689 - Ніколайчук О. (Видавничо-поліграфічний центр "Київський університет", 2014)
The materials of the collection of laws of Russian empire are examining as a source of the history of the Crimean campaigns 1687-1689. The informative potential of the legislative acts for researching of military and diplomatic preparation for campaigns, participation of the Ukrainian Cossacks and the state assessment of the results of the Crimean campaigns were analyzed in the article.

Розглянуто матеріали, вміщені в "Полном собрании законов Российской империи" як джерела з історії Кримських походів 1687–1689 рр. Проаналізовано інформативний потенціал законодавчих актів з вивчення військової та дипломатичної підготовки походів, участі в них українського козацтва, оцінки результатів воєнної кампанії з боку держави.
"Полное собрание законов Российской Империи" як джерело з історії Кримських походів 1687–1689 років
Keywords: edicts; Crimean campaigns; Cossacks; Tatars; укази; Кримські походи; козацтво; татари